2023
DOI: 10.1001/jamanetworkopen.2023.4885
|View full text |Cite
|
Sign up to set email alerts
|

Association of Electronic Cigarette Use by US Adolescents With Subsequent Persistent Cigarette Smoking

Abstract: ImportanceMany studies have reported a positive association of youth electronic cigarette (e-cigarette) use with subsequent cigarette smoking initiation, but it remains unclear whether e-cigarette use is associated with continued cigarette smoking after initiation.ObjectiveTo assess the association of youth baseline e-cigarette use with their continued cigarette smoking 2 years after initiation.Design, Setting, and ParticipantsThe Population Assessment of Tobacco and Health (PATH) Study is a national longitudi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
27
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 36 publications
0
27
0
Order By: Relevance
“…Given that cigarettes are overwhelmingly responsible for most tobacco-caused morbidity and mortality, addressing this research gap seems paramount. In this study, Sun and colleagues explore this important question and considered a variety of cigarette smoking patterns, as well as differences in absolute risk. Using data from the Population Assessment on Tobacco Use and Health (PATH) longitudinal cohort study, Sun et al studied more than 8000 cigarette-naive youths from waves 3 to 5.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Given that cigarettes are overwhelmingly responsible for most tobacco-caused morbidity and mortality, addressing this research gap seems paramount. In this study, Sun and colleagues explore this important question and considered a variety of cigarette smoking patterns, as well as differences in absolute risk. Using data from the Population Assessment on Tobacco Use and Health (PATH) longitudinal cohort study, Sun et al studied more than 8000 cigarette-naive youths from waves 3 to 5.…”
mentioning
confidence: 99%
“…In this study, Sun and colleagues explore this important question and considered a variety of cigarette smoking patterns, as well as differences in absolute risk. Using data from the Population Assessment on Tobacco Use and Health (PATH) longitudinal cohort study, Sun et al studied more than 8000 cigarette-naive youths from waves 3 to 5. They found that youths who had used e-cigarettes at baseline (wave 3) had higher odds of continued cigarette smoking, but the absolute risks of continued smoking at wave 5 were very small and did not significantly differ by baseline e-cigarette use.…”
mentioning
confidence: 99%
See 3 more Smart Citations